2017
DOI: 10.1136/heartjnl-2016-309852
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory whole-body vibration improves exercise capacity and physical performance in pulmonary arterial hypertension: a randomised clinical study

Abstract: ObjectiveIn patients with pulmonary arterial hypertension (PAH), supportive therapies may be beneficial in addition to targeted medical treatment. Here, we evaluated the effectiveness and safety of oscillatory whole-body vibration (WBV) in patients on stable PAH therapy.MethodsTwenty-two patients with PAH (mean PAP≥25 mm Hg and pulmonary arterial wedge pressure (PAWP)≤15 mm Hg) who were in world health organization (WHO)-Functional Class II or III and on stable PAH therapy for≥3 months, were randomised to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 32 publications
(38 reference statements)
4
42
0
1
Order By: Relevance
“…Mester et al [40] assumed that more efficient gas exchange and material metabolism between blood and muscle fibers (thanks to more opened capillaries immediately after WBV) could be one reason for increased oxygen uptake after exercise. In line with this, a WBV study in patients with pulmonary arterial hypertension revealed a VO 2peak increase after only 4 weeks' hospitalization [33]. Their exercise prescription resembled our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mester et al [40] assumed that more efficient gas exchange and material metabolism between blood and muscle fibers (thanks to more opened capillaries immediately after WBV) could be one reason for increased oxygen uptake after exercise. In line with this, a WBV study in patients with pulmonary arterial hypertension revealed a VO 2peak increase after only 4 weeks' hospitalization [33]. Their exercise prescription resembled our study.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, WBV induces involuntary, frequency-dependent, repeating eccentric, and concentric muscle contractions in the legs culminating in a tonic vibration reflex that enhances the recruitment of motor units during static or dynamic exercises [30,31]. Consequently, WBV, similar to low-intensity electrical muscle stimulation [32], enables high neuromuscular activity that can improve functional performance as well as cardiorespiratory fitness [33][34][35], may increase muscle strength [36], and is known to prevent muscle-mass loss during bed rest in healthy individuals [4,37]. In patients with chronic diseases like neurological, musculoskeletal, or metabolic disorders, WBV has proven to improve muscle strength, mobility, and balance [38].…”
Section: Considering That Muscular Capacity Is One Predictor Formentioning
confidence: 99%
“…Whole‐body vibration therapy can provide a significant improvement in reducing bone loss and reduce risk of falls in post‐menopausal women . Furthermore, its application improved exercise capacity, lower limb performance, and quality of life in patients with chronic diseases such as chronic obstructive pulmonary disease and pulmonary arterial hypertension . Thus, it would be of interest to assess the role of whole‐body vibration on body compartments as a feasible and easily accessible method of continuous and potentially home‐based physical exercise in patients with HF.…”
Section: Treatment Of Bone Loss In Heart Failurementioning
confidence: 99%
“…Based on the result of this study, muscle endurance after flexi bar training increased by doing 30-sec push up and 30-sec sit up test with statistical significance when comparing with moderate running exercise group at the end of the training. Gerhardt et al 39) suggested that resistance from vibration will help stimulate more blood circulatory transported for muscle and nerve cell nourishment. Moreover, repeating training postures frequently links between nerves and muscles to work together better.…”
Section: Discussionmentioning
confidence: 99%